Horizontal acquisition of endolithic symbionts: developing an experimental model - Hentz, Flora Morgana (2022)
Photosynthetic dinoflagellates from the family Symbiodiniaceae play a crucial role in coral reefs, as they establish trophic symbiosis with corals and other marine hosts. One of the biggest threats to the survival of coral reefs is coral bleaching, a process characterized by the expulsion of microalgal symbionts from their coral host that is driven by climate change. Recovery from bleaching is possible if hosts succeed in reestablishing symbiosis, e.g. by horizontally acquiring free-living symbiodiniaceans from the environment. In culture, free-living symbiodiniaceans commonly form an endolithic stage by encasing themselves into calcium carbonate deposits, so-called symbiolites. Recent work by the supervising team provided evidence that the same process occurs in reefs, as endolithic symbiodineaceans were found in reef sands around the world. To explore whether these endolithic populations could be a source of symbionts for cnidarian hosts, we presented Acropora tenuis coral juveniles and bleached Exaiptasia sp. anemones to compatible, symbiolite-producing strains. A. tenuis recruits were inoculated with free-living Cladocopium sp. (ITS2-type C1) cultures, isolated from coral tissue of the same species as part of this study. Recruits actively ingested the presented cells and established symbiosis within a few days. Other recruits were presented with symbiolites produced by a ITS2-Type C2 strain, which they held on their oral disk for up to 40 min and which they repeatedly ingested. Bleached anemones were presented with single symbiolites of Breviolum pseudominutum (ITS2-type B1), a compatible symbiont strain, which they ingested for up to 30 min. Symbiolites were imaged using a microscopy imaging-PAM fluorometer before and after ingestion, to assess the effects of being ingested on the size of symbiolites and the photosynthetic activity of endolithic cells. Following ingestion, symbiolites showed a trend for a reduced size, the number of endolithic cells was reduced, and the maximum quantum yield of remaining cells was unchanged, indicating that the missing cells vacated the structure. This study provides direct evidence for the release of endolithic symbiodiniaceans from symbiolites during their ingestion by cnidarian hosts, making the released cells accessible for the acquisition by the host to establish symbiosis.